Changes in incidence and prevalence of human papillomavirus in tonsillar and base of tongue cancer during 2000‐2016 in the Stockholm region and Sweden. Issue 6 (24th December 2018) - Haeggblom, Linnea; Attoff, Tove; Yu, Jingru; Holzhauser, Stefan; Vlastos, Andrea; Mirzae, Leila; Ährlund‐Richter, Andreas; Munck‐Wikland, Eva; Marklund, Linda; Hammarstedt‐Nordenvall, Lalle; Ye, Weimin; Ramqvist, Torbjörn; et al.
Abstract: Background: Tonsillar and base of tongue squamous cell carcinoma (TSCC/BOTSCC) has increased. In Stockholm, the proportion of human papillomavirus (HPV)‐positive cases and the incidence of TSCC rose between 1970 and 2006 then stabilized. Here, HPV‐prevalence, and TSCC/BOTSCC incidence 2000‐2016, in Stockholm and Sweden were followed. Methods: Incidence data for 2000‐2016 were obtained from the Swedish Cancer Registry. TSCC/BOTSCC biopsies, 2013‐2016 from Stockholm, were examined for HPV DNA and p16 INK4a, or data obtained from medical reports. For cases 2000‐2012, data were available from previous studies. Results: The incidence of TSCC/BOTSCC has continued to rise in Stockholm and Sweden 2000‐2016, especially after 2008. HPV DNA and p16 INK4a analysis was determined for 795 Stockholm cases from 2000 to 2016, with 72% being HPV DNA and p16 INK4a positive 2013‐2016, and 70% positive 2000‐2016. Conclusion: During 2000‐2016, especially after 2008, the incidence of TSCC/BOTSCC has continued to increase in Stockholm and Sweden, with an HPV‐prevalence of approximately 70% in Stockholm.